Combined ERP/fMRI Evidence For Early Word Recognition Effects In The Posterior Inferior Temporal Gyrus - Dien, Joseph (2013)
Two brain regions with established roles in reading are the posterior middle temporal gyrus and the posterior fusiform gyrus. Lesion studies have also suggested that the region located between them, the posterior inferior temporal gyrus (pITG), plays a central role in word recognition. However, these lesion results could reflect disconnection effects since neuroimaging studies have not reported consistent lexicality effects in pITG. Here we tested whether these reported pITG lesion effects are due to disconnection effects or not using parallel ERP/fMRI studies. We predicted that the Recognition Potential (RP), a left-lateralized ERP negativity that peaks at about 200–250 ms, might be the electrophysiological correlate of pITG activity and that conditions that evoke the RP (perceptual degradation) might therefore also evoke pITG activity. In Experiment 1, twenty-three participants performed a lexical decision task (temporally flanked by supraliminal masks) while having high-density 129-channel ERP data collected. In Experiment 2, a separate group of fifteen participants underwent the same task while having fMRI data collected in a 3T scanner. Examination of the ERP data suggested that a canonical Recognition Potential effect was produced. The strongest corresponding effect in the fMRI data was in the vicinity of the pITG. In addition, results indicated stimulus-dependent functional connectivity between pITG and a region of the posterior fusiform gyrus near the visual word form area (VWFA) during word compared to nonword processing. These results provide convergent spatiotemporal evidence that the pITG contributes to early lexical access through interaction with the VWFA.